FOREWORD - Gurgu, Elena (Annals of Spiru Haret University. Economic Series, 2018)
An escalation of protectionist measures in the middle of 2018 could spark a fresh downturn just as the global economy is picking itself up after the last one, the international body that represents the world’s central banks has warned. The Bank for International Settlements (BIS) said there were already signs that “the ratcheting up of rhetoric” was weighing on investment. It comes as USA president steps up hostility with some of the US’s key trading partners and allies, raising fears of a full-blown trade war.